2021
DOI: 10.18632/aging.203510
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of brain intrinsic activity in patients with hypertensive retinopathy: a resting-state fMRI study

Abstract: Objective: To investigate the changes of amplitude of low-frequency fluctuation (ALFF) in brain regions of patients with hypertensive retinopathy by using resting-state functional magnetic resonance imaging (rs-fMRI) and change in the relationship of ALFF value with potential emotional and psychological changes. Methods: Thirty-one patients with hypertensive retinopathy (HR) (16 men and 15 women) and 31 healthy controls (HCs; 16 men and 15 women) matched for age, sex, and weight were enrolled in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our previous studies [ 13 15 ] found that some ophthalmic diseases can cause brain regional changes. Using fMRI, researchers found that DE may lead to dysfunction of specific brain regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies [ 13 15 ] found that some ophthalmic diseases can cause brain regional changes. Using fMRI, researchers found that DE may lead to dysfunction of specific brain regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study has reported that lobules VI and VII of the vermis, also referred to as the oculomotor vermis, play a crucial role in saccade adaptation [37]. Furthermore, lesions in the cerebellar vermis may lead to balance disorders because of its connections with the spinal cord and vestibular nucleus [38]. In conclusion, these findings align with our study results, suggesting that the decline in fALFF values in the right cerebellar Crus2 and the amplified ALFF values in the left cerebellar region 6 and vermis_7 may be linked to compromised optic nerve function and impaired balance movement in individuals with CRAO.…”
Section: Discussionmentioning
confidence: 99%
“…Several rs-fMRI metrics are available for measuring the regional intensity of spontaneous LFFs. Amplitude of low-frequency uctuation (ALFF) (Zang et al, 2007), can directly re ect the intensity of spontaneous neural activity and has been applied widely in eye diseases including glaucoma (Peng et al, 2021), strabismus (Min et al, 2018), retinal vein occlusion (Wu et al, 2019), and hypertensive retinopathy (Hu et al, 2021). ALFF has also been proven to have moderate to high test-retest reliability primarily in gray matter (Zou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, most rs-fMRI studies adopting the methods above investigated LFFs amplitude at traditional frequency band (0.01-0.08 Hz) (Hu et al, 2021;Min et al, 2018;Peng et al, 2021), because this frequency band was thought to be related to neuronal uctuations (Biswal et al, 1995;D. Zhang & Raichle, 2010).…”
Section: Introductionmentioning
confidence: 99%